2021
DOI: 10.1016/j.thromres.2020.10.031
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anticoagulation on clinical outcomes in novel Coronavirus (COVID-19) pneumonia in a U.S. cohort

Abstract: Background: COVID-19 infection is associated with D-dimer elevations, high rates of thrombus formation, and poor clinical outcomes. We sought to determine if empiric therapeutic anticoagulation (AC) affected survival in COVID-19 patients compared to standard prophylactic AC. Methods: Retrospective analysis of 402 COVID-19 patients hospitalized between March 15 and May 31, 2020 was performed. Clinical outcomes were compared between 152 patients treated with therapeutic AC to 250 patients on prophylactic AC. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 10 publications
(12 reference statements)
2
66
2
4
Order By: Relevance
“…It may be that the primary driver of mortality in these patients is the degree of severity of infection rather than initiation of therapeutic anticoagulation. 40 Availability, feasibility, affordability, and safety. Guidelines for chemoprophylaxis for non-COVID-19 cases in LMICs frequently are in accordance with recommendations from HICs.…”
Section: What Type Of Venous Thromboembolism (Vte) Prophylaxismentioning
confidence: 99%
“…It may be that the primary driver of mortality in these patients is the degree of severity of infection rather than initiation of therapeutic anticoagulation. 40 Availability, feasibility, affordability, and safety. Guidelines for chemoprophylaxis for non-COVID-19 cases in LMICs frequently are in accordance with recommendations from HICs.…”
Section: What Type Of Venous Thromboembolism (Vte) Prophylaxismentioning
confidence: 99%
“…We read with interest the study by Lynn et al among 402 hospitalized COVID-19 patients, which did not show any survival benefit in those who were administered therapeutic dosage of anticoagulation (AC) compared to standard thromboprophylaxis [ 1 ]. It should be mentioned that the study had retrospective design and therapeutic AC was empirically prescribed mainly to patients with severe COVID-19, especially those admitted to Intensive Care Unit (ICU) [ 1 ].…”
mentioning
confidence: 99%
“…We read with interest the study by Lynn et al among 402 hospitalized COVID-19 patients, which did not show any survival benefit in those who were administered therapeutic dosage of anticoagulation (AC) compared to standard thromboprophylaxis [ 1 ]. It should be mentioned that the study had retrospective design and therapeutic AC was empirically prescribed mainly to patients with severe COVID-19, especially those admitted to Intensive Care Unit (ICU) [ 1 ]. Another retrospective study including 4389 COVID-19 patients, showed that the administration of prophylactic or therapeutic AC therapy was associated with lower in-hospital mortality and intubation compared with no AC; however, in a sub-analysis including patients initiating AC ≤48 h from admission, no significant difference was observed between therapeutic and prophylactic AC, despite a trend in favor of the former [ 2 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations